Fixed-Wing Aeromedical Evacuation of a Child With a Subtrochanteric Femur Fracture Immobilized Using Static Splints in a Resource-Limited Setting: A Case Report - Ghani Abdurahim (Perkumpulan Kedokteran Militer, 2026)
Background: Subtrochanteric femur fractures are serious injuries associated with significant morbidity and, occasionally, mortality. Appropriate pre-hospital immobilization is essential to prevent secondary injury during patient transport. In resource-limited, geographically isolated settings, the success of immobilization depends not on device sophistication but on the correct application of available materials. Case Illustration: A 7-year-old female sustained a subtrochanteric right femur fracture following a high-energy motor vehicle accident on Natuna Island, Indonesia. The patient underwent aeromedical evacuation via military fixed-wing aircraft. The injured limb was immobilized using static rigid splints spanning the hip and knee joints, with the patient secured supine on a semi-rigid mattress using multi-point bandage fixation. Following an approximately two-hour flight, post-arrival radiographs confirmed no fracture displacement or new injury. The patient remained stable with no worsening pain, and subsequently underwent successful open reduction and internal fixation. Discussion: Fracture stability was maintained through immobilization spanning both the hip and knee joints, which neutralizes the deforming muscular forces acting on the proximal femoral fragment. Four technical elements were critical: splint length sufficient to bridge both joints, bilateral medial and lateral placement, padding at bony prominences, and five-point bandage fixation. Traction splinting was intentionally avoided given its recognized aeromedical contraindications. Conclusion: Properly applied static rigid splinting can maintain fracture stability throughout fixed-wing aeromedical evacuation in resource-limited settings. Correct execution of technique, rather than sophistication of materials, is the primary determinant of safe transport outcomes.